The quest for Magrathea planets: I. Formation of second-generation exoplanets around double white dwarfs - Ledda, Sebastiano; Danielski, Camilla; Turrini, Diego (Astronomy and astrophysics (Berlin), 2023)
Context. The formation of planets around binary stars is the subject of ongoing investigations focusing on the early stages of stellar life. The evolution of binaries that become double white dwarfs (DWDs), however, can cause the ejection of high amounts of dust and gas. This material can give rise to circumbinary discs and become the cradle of new planets, yet no studies to date have focused on the formation of circumbinary planets around DWDs. These binaries will be the main sources of gravitational waves (GWs) detectable by the Laser Interferometer Space Antenna (LISA) mission from the European Space Agency (ESA), opening the possibility to detect circumbinary planets around short-period DWDs everywhere in the Milky Way and in the Large Magellanic Cloud via the modulation of their GW signal. Aims. We investigated the formation process and characteristics (e.g. formation times, masses, and final locations) of Magrathea planets within circumbinary discs around detached DWDs, paying particular attention to the formation of gas giant (GG) planets. Methods. We simulated multiple planet formation tracks to explore how the planetary formation processes typical of pre-main sequence (pre-MS) discs are affected by the disc environments surrounding DWDs. We investigate the mass and orbital evolution of planetary seeds growing first through pebble accretion, then by gas accretion. Our growth tracks account for both the disc accretion rate onto the central binary and the disc photoevaporation rate caused by stellar irradiation. Results. We present both planetary formation tracks taking place in steady-state discs, and formation tracks taking place in discs evolving as a function of time. Our simulations show that planetary formation should be common in circumbinary discs around DWDs, but the formation of GG planets can be hindered by the temperatures of the disc and the rapid disc depletion. Conclusions. Our results show that planetary formation in circumbinary discs around DWDs can be possible. In particular, the extreme planetary formation environment implies three significant results: (i) the accretion rate and the metallicity of the disc should be high in order to form sub-stellar objects with masses up to ~31 M J , this is achieved only if planet formation starts soon after the onset of the disc and if first-generation seeds are present in the disc; (ii) seeds formed within 0.1 Myr, or within 1 Myr, of the onset of the disc can only produce sub-Neptunian (SN) planets and Neptunian (N) planets, unless the disc accommodates first-generation seeds with mass 10 M ⊕ ; (iii) most of the planets are finally located within 1 au of the disc centre, while they are still undergoing the gas accretion phase.